A Realist Philosophy of Social Science Explanation and Understanding - Manicas, Peter T (Cambridge University Press, 2013)
This volume reassesses the problem of explanation in social science from what remains a marginalized, realist perspective. Because the problem of explanation is central to inquiry in social science, the volume also provides a systematic philosophy of social science. It begins with the idea that the fundamental goal of theory in both the natural and social sciences is not, contrary to widespread opinion, prediction and control, or the explanation of events (including “behavior”). Rather, more modestly, theory (at least in one of its clear senses) aims to provide an understanding of the processes which jointly produce the contingent outcomes of experience